Strategi Marketing Public Relations Dalam Meningkatkan Penerimaan Peserta Didik Baru Melalui Media Sosial Instagram @Alhamidiyah_Official (International Forum of Researchers and Lecturers, 2024)
Al-Hamidiyah Islamic Foundation's Instagram still needs a Marketing Public Relations strategy to increase the acceptance of new students. Marketing Public Relations at the Educational Institutions of the Al-Hamidiyah Foundation is needed because educational institutions need to convince prospective students due to the lack of public relations efforts to expose the message of the Al-Hamidiyah Foundation via Instagram. This study aims to determine the pull strategy, push strategy, and pass strategy used by Al-Hamidiyah's Marketing Public Relations. This study uses a descriptive analysis method with a qualitative approach. The data collection techniques used are interviews, observation, and literature studies. This study uses the theory of Marketing Public Relations namely Thomas L. Harris Pull, Push, and Pass Strategy. The results of this study are that the Pull Strategy provides prizes in the form of vouchers or gift cards by following the Al-Hamidiyah account through trivia quizzes, or giveaway, promoting advertisements/Instagram Ads. The Push Strategy is cooperating in posting content with influencers or media partners, sharing student activity content, outstanding students and facilities. The Pass Strategy is carrying out the blue ocean strategy & sharing learning program content and student activities.